SOSIALISASI DAN EDUKASI PENGELOLAAN SAMPAH DI DESA PEMECUTAN KAJA - Ida Ayu Putu Sri Mahapatni; Ni Putu Trisna Windika Pratiwi (JURNAL SEWAKA BHAKTI, 2026)
Sustainable waste management is key to reducing negative impacts on the environment. Waste management socialization and education are a form of community service carried out by the Hindu University of Indonesia through the Thematic Community Service Program (KKN) "Jagat Kerthi" which carries the theme of Harmonization of the Universe. The issue of harmonizing the universe is certainly inseparable from the problem of waste which is very closely related to people's daily lives so that if not managed properly it can certainly have a negative impact on the environment. Through this socialization and education, the community, especially the PKK women of Pemecutan Kaja Village, will gain information and knowledge regarding the importance of independent waste sorting and the reactivation of the Waste Bank in Pemecutan Kaja Village as an initial step that can be taken in sustainable waste management and for environmental sustainability.